2005
DOI: 10.1103/physrevlett.95.035001
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for the Study of Thermophysical Properties of High-Energy-Density Matter Using Current and Future Heavy-Ion Accelerator Facilities at GSI Darmstadt

Abstract: The subject of high-energy-density (HED) states in matter is of considerable importance to numerous branches of basic as well as applied physics. Intense heavy-ion beams are an excellent tool to create large samples of HED matter in the laboratory with fairly uniform physical conditions. Gesellschaft für Schwerionenforschung, Darmstadt, is a unique worldwide laboratory that has a heavy-ion synchrotron, SIS18, that delivers intense beams of energetic heavy ions. Construction of a much more powerful synchrotron,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
74
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 167 publications
(74 citation statements)
references
References 10 publications
0
74
0
Order By: Relevance
“…The key parameters related to HEDP research at the HIAF and other advanced heavy ion drivers are listed in Table 1, where E 0 , N , E total , S f , t, and E ρ are the particle energy, the beam intensity (in units of ppp), the total beam energy per pulse, the FWHM of the beam spot, the pulse duration, and the energy density in a lead target, respectively [2][3][4] .…”
Section: High Intensity Heavy-ion Accelerator Facility (Hiaf)mentioning
confidence: 99%
See 1 more Smart Citation
“…The key parameters related to HEDP research at the HIAF and other advanced heavy ion drivers are listed in Table 1, where E 0 , N , E total , S f , t, and E ρ are the particle energy, the beam intensity (in units of ppp), the total beam energy per pulse, the FWHM of the beam spot, the pulse duration, and the energy density in a lead target, respectively [2][3][4] .…”
Section: High Intensity Heavy-ion Accelerator Facility (Hiaf)mentioning
confidence: 99%
“…Email: zhaoyt@impcas.ac.cn by methods of high energy proton/ion radiography and in fast ignition of a compressed fuel. Associated investigations have been pursued with increasing intensity by major accelerator laboratories and institutions in Europe, the USA, Russia, and Japan, where significant progress has been made during the last few decades [1][2][3][4][5][6][7][8][9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…This shows that a substantial progress in the technology of high intensity bunched beams is required to achieve ion beam ICF. However, theoretical work that includes sophisticated two-and three-dimensional numerical simulations as well as analytic modeling [15][16][17][18][19][20][21][22][23][24][25][26][27][28] has shown that one can carry out very useful work in the field of high energy density ͑HED͒ physics using the existing ion beam facilities and those which will be available in the foreseeable future.…”
Section: Introductionmentioning
confidence: 99%
“…HED states in matter is a very important subject with very wide applications to numerous fields in basic and applied physics, as well as it has great potential for different important industrial applications (Tahir et al, 1999(Tahir et al, , 2000a(Tahir et al, , 2000b(Tahir et al, , 2001a(Tahir et al, , 2001b(Tahir et al, , 2005c(Tahir et al, , 2005dPiriz et al, 2002Piriz et al, , 2003aPiriz et al, , 2003bPiriz et al, , 2006Piriz et al, , 2007aPiriz et al, , 2007bTemporal et al, 2003Temporal et al, , 2005Lopez Cela et al, 2006;Hoffmann et al, 2005).…”
Section: Introductionmentioning
confidence: 99%